Creation Music Blahmanukan | Tabuh Kreasi Pepanggulan Blahmanukan - Made Wahyu Arya Wisesa (GHURNITA: Jurnal Seni Karawitan, 2023)
Blah means broken or separated, and manuk with the ending -an, which means bird. So, Blahmanukan is a bird split / divided into two parts. From this concept, the creator put the idea into Barungan Gong Kebyar Pacek with the title Tabuh Kreasi Pepanggulan Blahmanukan; this composition of Tabuh Kreasi Pepanggulan prioritizes melodic, rhythmic, dynamic, and energetic patterns as if describing how beautiful the bird is, seen from the singing of birds. Melodious and agile, the bird flies. The tabuh of this pepanggulan creation is contemporary by prioritizing originality and referring to traditional patterns or standards such as pengawit, gineman, pengawak, retailer, and pekaad, from these traditions, the creator processes the elements of the content, playing techniques on the instrument gangsa pemade, melody breaker, jublag, jegogan, and flute, as well as processing of tempo, by using more diatonic melody playing, playing drums, and playing kebyaran in each part. The novelty lies in the maximum extent of the creator's ability to package the work.